Association between XRCC3 rs861539 Polymorphism and the Risk of Ovarian Cancer: Meta-Analysis and Trial Sequential Analysis. (8th August 2022) - Hu, Siya; Jing, Yunnan; Liu, Fangyuan; Han, Fengjuan
Abstract : Background. Current studies on the relationship between XRCC3 rs861539 polymorphism and ovarian cancer risk have been inconsistent. Therefore, we performed a meta-analysis to explore their association. Methods. Six electronic databases (PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, and China Wanfang Database) were searched for relevant studies published before December 2021. Meta-analysis, subgroup analysis, sensitivity analysis, and publication bias analysis were performed using Stata software 16.0. Trial sequential analysis (TSA) was performed using TSA 0.9.5.10 Beta software. Results. A total of 12 studies were included in 9 literatures, comprising 4, 634 cases of ovarian cancer and 7, 381 controls. After Bonferroni correction, the meta-analysis showed an association between XRCC3 rs861539 polymorphism and ovarian cancer risk in the heterozygote model and the dominant model (GA vs. GG: OR = 0.88, 95 % CI = 0.81 -0.96, P = 0.003 ; GG vs. GA+AA: OR = 0.89, 95 % CI = 0.82 -0.96, P = 0.004 ). In an ethnically stratified subgroup analysis, XRCC3 rs861539 was shown to reduce the risk of ovarian cancer in Caucasian in the heterozygote model and the dominant model (GA vs. GG: OR = 0.88, 95 % CI = 0.81 -0.96, P = 0.004 ; GG vs. GA+AA: OR = 0.88, 95 % CI = 0.81 -0.96, P = 0.004 ). In the control source and detection method stratified subgroup analysis, hospital-based studies and PCR-RFLP-based studies were found to increase ovarian cancer risk (GG vs. AA: OR = 1.30, 95 % CI = 1.05 -1.62, P = 0.016 ; GG vs. AA: OR = 1.31, 95 % CI = 1.06 -1.62, P = 0.013 ). Conclusion. This meta-analysis showed a significant association between XRCC3 rs861539 polymorphism and ovarian cancer risk, especially in Caucasians. Large-scale multicenter case-control studies in more different regions will be needed in the future.